THE PREVALENCE OF ATRIAL FIBRILLATION CAUSES; A CROSS-SECTIONAL SURVEY AT A LARGE TEACHING HOSPITAL - MAJEED, U; AHMAD, R; AQEEL, M; KHAN, S; KANWAL, S; BASHIR, MA (Biological and Clinical Sciences Research Journal, 2024)
The most frequent cause of atrial fibrillation is abnormalities or damage to the heart’s anatomy. Previous observations suggest that the prevalence of atrial fibrillation may be understated in high-income countries compared to low- and middle-income nations. Conversely, other findings indicate that the prevalence of atrial fibrillation in developed countries may be overstated compared to third-world countries. Objective: To determine the frequency of causes of atrial fibrillation in a tertiary care hospital and to evaluate the prevalence of atrial fibrillation etiology in this setting. Methods: This cross-sectional survey, conducted with a rigorous methodology, was carried out in the Department of Cardiology at Gulab Devi Hospital, Lahore, Pakistan, over six months, from December 18, 2018, to June 18, 2019. After receiving clearance from the hospital ethics committee, 250 patients diagnosed with atrial fibrillation and meeting the inclusion criteria were enrolled in the study. Written consent was obtained from all participants, and their demographics were recorded. Patients underwent ECG, ECHO, and other clinical assessment tests to evaluate the various causes of atrial fibrillation. Detailed histories of potential etiological factors were recorded using a structured proforma. Data were analyzed using appropriate statistical methods. Results: The mean age of the patients was 35.03 ± 12.29 years. Among the studied causes of atrial fibrillation, the prevalence of coronary kidney disease, diabetes mellitus, and hypertension were notably high, at 66%, 52.4%, and 41.4%, respectively. Other significant causes included coronary artery disease (12.4%), presyncope (13.2%), obesity (18%), and valvular disease (21.6%). Conclusion: The findings of this study revealed that the most prevalent causes of atrial fibrillation among the study population were coronary kidney disease, diabetes mellitus, and hypertension. Other significant etiological factors included coronary artery disease, presyncope, obesity, and valvular disease. These results highlight the need for targeted management strategies for atrial fibrillation in tertiary care settings.